Efeitos da diminuição do tamanho médio de partículas da frita nas propriedades dos esmaltes cerâmicos visando aplicação na esmaltação digital - Nieves, Leidy Johana Jaramillo (Universidade Federal de São Carlos, 2017)
Nowadays Brazil is the second largest producer and consumer of ceramic tiles in the world. In the process of tile’s production, the decoration and glazing play a prominent role since they are responsible for technical and aesthetic properties of the product. Ceramic tile decoration underwent a revolution with the arrival of ink-jet technology. This technology has also started to become a focus of interest for glazing, creating the possibility of having a completely digital line in the manufacture processing. Accordingly, glazes must be adapted to requirements of this new technology. Among them, the particle size of the suspensions employed in the ink jet technology should be lower than that used in traditional glazes. In this context, this project evaluates the effect of the average particle size reduction on the properties of glazes, from their preparation, application, sintering and final product. The methodology of the project consisted in using an industrial frit applied to transparent glazes. The frit was ground to obtain four different granulometry particle sizes for the preparation of glazes. The materials were characterized by rheological analysis, applied layer and their interaction with digital inks. Finally, the sintering process and the characteristics of the fired product were monitored. The study showed that the main effect of the decrease in particle size was on the particle size distribution curve, which affected the packing of particles and this, in turn, affects the pore structure which affects the packing of the suspension, That is, rheological behavior and the characteristics of the applied layer of the glazes, showing that changes in the applied layer affected the subsequent stage as the decoration and the firing.
Effects of particles size reduction of frit in the properties of ceramic glazes aiming application in digital glazing
Keywords: Frita; Distribuição de tamanho de partículas; Empacotamento; Permeabilidade; Sinterização; Frit; Particles size distribution; Packing; Permeability; Sintering; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA